Quo Vadis, Civil Partnership? - Scherpe, Jens M (Victoria University of Wellington Law Review, 2015)
This article discusses and compares the different concepts of civil partnership around the globe: either as functional equivalent to marriage for same-sex couples only or as an alternative to marriage for all couples. It analyses its declining role in the wake of widespread marriage equality reforms and then discusses, in particular, the current position of England and Wales, and Scotland, where ill-conceived law reform has led to a situation in which same-sex couples are privileged and opposite-sex couples are discriminated against.